Effects of different surgical strategies and left ventricular remodelling on the outcomes of coronary artery bypass grafting in heart failure patients with reduced ejection fraction - Cao, Jian; Yu, Miao; Xiao, Yu; Dong, Ran; Wang, Jiayang (Frontiers in Cardiovascular Medicine, 2024)
Background:Ischaemic heart failure with reduced ejection fraction(HFrEF)caused by coronary artery disease accounts for the largest proportion of heart failure cases with the worst prognosis.Coronary artery bypass grafting(CABG)is the most effective treatment for ischaemic HFrEF.On-pump and off-pump are the two surgical methods used for CABG.Whether patients with HFrEF should undergo on-or off-pump CABG is controversial in coronary heart disease surgery.The left ventricular end-systolic volume index(LVSEVI)is the gold standard for evaluating the severity of left ventricular remodelling;however,its effect on the perioperative risk and long-term survival rate of patients with HFrEF undergoing CABG remains unclear.Methods:This single centre prospective cohort analysis included 118 coronary heart disease patients with symptoms and signs of heart failure and a left ventricular ejection fraction (LVEF) of<40%who were enrolled consecutively from January 2019 to December 2023. Operative mortality,perioperative complications,and long-term survival were compared among patients treated with various LVESVIs and surgical methods.The primary outcomes were cardiac death, myocardial infarction,heart failure,stroke, and revascularization(percutaneous coronary intervention or redo CABG)with a median follow-up of 38±10 months.The 30-day postoperative mortality of 118 patients was 6.8%.Patients in the off-pump group had significantly higher perioperative mortality than those in the onpump group(12.5% vs. 3.8%, p=0.03).In the off-pump group, a higher proportion of patients required perioperative mechanical assistance, such as intra-aortic artery balloon pump (IABP) or extracorporeal membrane oxygenation(ECMO),compared to those in the on-pump group.Patients in the off-pump group were more likely to have postoperative atrial fibrillation(AF).In the on-pump group,the incidence of postoperative AF and IABP use were significantly higher in patients with more severe left ventricular remodelling than in those with less severe left ventricular remodelling.In the off-pump group,patients with more severe left ventricular remodelling had higher ECMO usage,incidence of postoperative AF,and perioperative mortality.Major adverse cardiac event (MACE)-free survival rate was significantly higher in the on-pump group than in the off-pump group and there was no significant difference in MACE free survival rates between the two groups of patients with different degrees of left ventricular remodelling.On-pump bypass is a better surgical procedure for patients with ischaemic HFrEF,especially those with severe left ventricular remodelling.Left ventricular remodelling increases perioperative mortality but has no effect on long-term survival.